Trees count - P. Ptolemy (pseud.) (Australasian Accounting, Business and Finance Journal, 2008)
There's carbon in the atmosphere, it's rising as we speak. It's past three eighty parts per mil, and heading for a peak. It's higher than it's ever been, than we've ever seen before. Says old air trapped in ice, from an Antarctic core. The Arctic ice is melting, and the sea is on the rise. We've got to slow emissions; we've got to stabilise.